(3GNJUGQ cJGH GdCZPjI (B( (3MjdI GdHQA (B) (3dLGdjfhSs - (3CHi YeQGf ehSi Hf YHjO Gddg Hf ejehfs
(3ChdgG (B:s
(3gPG cJGH djS GaJbGQg Edi GdGNJUGQ HGdYXje , hPdc dCf Gdbhi GdJi jYddgG HgG ef bhI cd ZPGA djS ajgG JcKjQ aGMT , hdG GdJcQjQ GdPi LQJ YGOJg Hg s
(3BNQgG (B:s
(3hCeG GdeGA GdfGRd ai GdYjf aEfg eG OGe ai Chd fRhdg bO jJYdd , hCeG EPG fRd hGSJMce adjS jJMdd s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B5 s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdWHs